Morphometric Dimensions of the Maximum Length of Maxillary Air Sinus in Adult Bangladeshi Population - Mourin, Nusrath; Rahman, Mushfika; Mannan, Fahmida; Mowtoshee, Nusrat Rumman; Sultana, Afroza; Akter, Ferdousi (Community Based Medical Journal, 2026)
A cross-sectional, analytical type of study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka, Bangladesh, from July 2019 to June 2020, to determine the maximum length of maxillary air sinus in a Bangladeshi population. Our study samples were 90 Bangladeshi nationals who were attending the Radiology & Imaging Department of the same institution. We adopted convenient sampling method. The maximum length of the right and left maxillary air sinus were measured by the longest distance from the most anterior point of the anterior wall to the most posterior point of the posterior wall by using MB-Ruler for Windows software. The maximum length of right maxillary air sinus in male was significantly higher than that of female (p=0.014). However, no such difference was observed in the maximum length of left maxillary air sinuses between male and female (p=0.137). The maximum length of right maxillary air sinus was significantly higher than that of the left maxillary air sinus in males (p=0.001). However, no difference was observed in the maximum length between the right and the left maxillary air sinuses in females (p=0.099). CBMJ 2026 January: vol. 15 no. 01 P:56-60